STUDI KOMPETENSI KEWIRAUSAHAAN MAHASISWA PERGURUAN TINGGI DI JAWA BARAT - Yoni Hermawan, - (2023)
The problem studied in this study is the entrepreneurial competence among students who are involved in the entrepreneurship training and learning process on campus. The aim of this study was to test a number of key theories. Theories that need to be tested are "Theory of Planned Behavior" from Icek Ajzen, and "Theory of Entrepreneurial Events" from Francisco Linan and Shapero, and Sokol. Specifically, the "Entrepreneurial Behavior and Entrepreneurial Competencies Extention Models" approach is used to show how strong Entrepreneurial Education, Entrepreneurial Intention, Self-Efficacy, and Entrepreneurial Orientation affect the variables that make up Entrepreneurial Competencies. The research approach used in this research is quantitative with an explanatory survey method. The population in this study were students at Siliwangi University, Galuh University, Kuningan University and Garut University, who had taken entrepreneurship courses with a population size of 6880 students. The sample size is 378 respondents with a sampling technique using the Proportionate Random Sampling method. The results showed that entrepreneurship education had a positive effect on entrepreneurial intention, self-efficacy and entrepreneurial orientation. And entrepreneurial intention, self-efficacy and entrepreneurial orientation partially mediate the influence of entrepreneurship education on entrepreneurial competence. This means that the more effective entrepreneurship education, the higher entrepreneurial competence along with the higher levels of entrepreneurial intention, self-efficacy and entrepreneurial orientation.